2019
DOI: 10.3390/plants8120540
|View full text |Cite
|
Sign up to set email alerts
|

Exogenously-Sourced Ethylene Modulates Defense Mechanisms and Promotes Tolerance to Zinc Stress in Mustard (Brassica juncea L.)

Abstract: Heavy metal (HM) contamination of agricultural soil is primarily related to anthropogenic perturbations. Exposure to high concentration of HMs causes toxicity and undesirable effects in plants. In this study, the significance of ethylene was studied in response of mustard (Brassica juncea) to a high level (200 mg kg−1 soil) of zinc (Zn) exposure. Plants with high Zn showed inhibited photosynthesis and growth with the increase in oxidative stress. Application of ethylene (as ethephon) to Zn-grown plants restore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 67 publications
2
37
0
Order By: Relevance
“…Indeed, it has been reported that ethephon at 50 and 100 ppm increased protein band intensities compared to untreated plants of broad bean [ 62 ]. The higher leaf area observed ( Table 5 ) was likely correlated with ethephon-enhanced ethylene biosynthesis ( Figure 1 ), as also found in other studies [ 45 , 47 ].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Indeed, it has been reported that ethephon at 50 and 100 ppm increased protein band intensities compared to untreated plants of broad bean [ 62 ]. The higher leaf area observed ( Table 5 ) was likely correlated with ethephon-enhanced ethylene biosynthesis ( Figure 1 ), as also found in other studies [ 45 , 47 ].…”
Section: Discussionsupporting
confidence: 86%
“…Ethylene plays a role in regulating synthesis of S compounds and controls plant processes and stress tolerance [ 19 , 47 ]. It has been reported that ethylene interacts with Se and improves the antioxidant system under Cd stress by inducing defense responses [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results after 30 DAS revealed that exposure to Zn stress causes toxicity by inhibiting photosynthesis and growth, while increasing the oxidative stress biomarkers. ET application (as ethephon) to Zn-stressed plants restored photosynthesis and growth of mustard plants by decreasing oxidative stress via augmenting antioxidant activity, the metabolism of proline, glyoxalase system, and optimum nutrient homoeostasis [89]. In tomato plants, Alves et al [90] provided new insights into the interactive role of ET on selenium-mediated antioxidant enzymes under Cd stress.…”
Section: Role Of Ethylenementioning
confidence: 99%